STUDY OF THE PROBLEMS OF ATMOSPHERIC WASTE WATER COLLECTION AND GREEN FIELD IRRIGATION - AKHUNOV, DANIYOR (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
All over the world today the problem of water scarcity is getting worse. At the moment, we see that in the countries of Central Asia, as well as in our republic, the shortage of water is increasing, the melting of ice reserves is accelerating, the level of reserves of river, stream, lake and groundwater is decreasing, and green spaces are shrinking. One of the most important problems is the prevention of water shortages and the establishment of an effective use of atmospheric wastewater in the water supply of green spaces.